Glucosinolates From Cruciferous Vegetables and Their Potential Role in Chronic Disease: Investigating the Preclinical and Clinical Evidence - Connolly, Emma L.; Sim, Marc; Travica, Nikolaj; Marx, Wolfgang; Beasy, Gemma; Lynch, Gordon S.; Bondonno, Catherine P.; Lewis, Joshua R.; Hodgson, Jonathan M.; Blekkenhorst, Lauren C. (Frontiers in Pharmacology, 2021)
An increasing body of evidence highlights the strong potential for a diet rich in fruit and vegetables to delay, and often prevent, the onset of chronic diseases, including cardiometabolic, neurological, and musculoskeletal conditions, and certain cancers. A possible protective component, glucosinolates, which are phytochemicals found almost exclusively in cruciferous vegetables, have been identified from preclinical and clinical studies. Current research suggests that glucosinolates (and isothiocyanates) act via several mechanisms, ultimately exhibiting anti-inflammatory, antioxidant, and chemo-protective effects. This review summarizes the current knowledge surrounding cruciferous vegetables and their glucosinolates in relation to the specified health conditions. Although there is evidence that consumption of a high glucosinolate diet is linked with reduced incidence of chronic diseases, future large-scale placebo-controlled human trials including standardized glucosinolate supplements are needed.